The Method of Qura’nic Interpretation – Historical Perspective - Gafoordeen, N. (My University, 2017)
There are numerous forms of explanation for qur’anic verses existing by the Muslim Intellectuals since reveled of holy Quran since 7th century. This manuscript attempts to present greatest proper approaches of explanation employed by the Mufassiroon. Using content analysis procedures and expressive attitude, the expansion of tafsir since prophet Mohamed period to 20th century are explored and described systematically Outcome indicates that there are seven methods of interpretation used mostly to explain meaning of the verses of holy quran. Entire methods are divided into three basic groups: Tafsir bi-l-riwaya, tafsir bi-l-diraya and Tafsir bi-lishara. The works of the mufessireen Quranic exegesis should also be appreciated in order to remain aware of the meaning of the holy Quran upon which all expiation rests.
Keywords: Interpretation, Methodology, Tafsir-riwaya, Tafsir- diraya